Sense of neighborhood belonging and health: geographic, racial, and socioeconomic variation in Wisconsin - Clark, Joseph A.; Engelman, Michal; Schultz, Amy A.; Bersch, Andrew J.; Malecki, Kristen (Frontiers in Public Health, 2024)
Background Individuals’ sense of belonging (SoB) to their neighborhood is an understudied psychosocial factor that may influence the association between neighborhood characteristics, health, and disparities across socio-demographic groups. Methods Using 2014–2016 data from the Survey of the Health of Wisconsin (SHOW, N = 1,706), we conduct a detailed analysis of SoB and health in an American context. We construct OLS and logistic regressions estimating belonging’s association with general, physical, and mental health. We explore geographic, racial, and socioeconomic variation to understand both the differential distribution of SoB and its heterogeneous relationship with health. Results A higher SoB is positively associated with better physical, mental, and general health. White participants report higher SoB than Black participants, yet the association between SoB and mental health is strongest among participants of color and urban residents. Conclusion Sense of belonging to neighborhood significantly predicts many facets of health, with place and individual characteristics appearing to moderate this relationship. Racial, geographic, and socioeconomic disparities in belonging-health associations raise important questions about who benefits from the social, economic, and physical aspects of local communities.